Association of longitudinal repeated measurements of frailty index with mortality: cohort study among community-dwelling older adults - Li, Xiangwei; Schöttker, Ben; Holleczek, Bernd; Brenner, Hermann (EClinicalMedicine, 2022)
Frailty indices (FIs), defined by accumulation of health deficits, have been shown to be strongly related to mortality in older adults. However, previous studies mostly relied on FI measurement at a single point of time. We aimed to investigate the association of frailty with mortality according to longitudinal repeated measurements of FI in a large population-based cohort study in Germany.